2021
DOI: 10.1016/j.onehlt.2021.100256
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus infection in high-risk populations in Osun State, Nigeria

Abstract: Hepatitis E virus (HEV) infection is an emerging infection that is of major public health concern, especially in some vulnerable groups like immunosuppressed individuals, pregnant women and HBV-coinfected individuals. HEV is transmitted faecal/oral or zoonotically depending on the HEV-genotype. This study aimed at investigating HEV infections among different at-risk populations in Osun State, Southwestern Nigeria. A total of 720 serum samples were collected from animal handlers, pregnant women, people living w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…They visit waste heaps and stagnant or flowing water bodies thereby contaminating such areas with feces and urine. This system predisposes swine to diverse infections including HEV and thus facilitates subsequent transmission to humans, especially in environments where there are close association of swine and people (19,28). This detection in poultry birds could also result in commercial chicken farmers incurring losses in their businesses (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They visit waste heaps and stagnant or flowing water bodies thereby contaminating such areas with feces and urine. This system predisposes swine to diverse infections including HEV and thus facilitates subsequent transmission to humans, especially in environments where there are close association of swine and people (19,28). This detection in poultry birds could also result in commercial chicken farmers incurring losses in their businesses (41).…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, varying prevalences of HEV infections have also been documented in different States; Jos-42.7% (23); Oyo-1.7% (24); Ekiti-13.4% (25); Osun-43% (26) and Lagos-17.8% (27). These infections have mostly been linked to human populations (9,17,28,29). Just a few studies have documented HEV in animals in Nigeria (17).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to European countries, HEV transmission in Africa has traditionally been associated with large outbreaks caused by contaminated water consumption and inadequate sanitation practices ( Bagulo et al, 2018 ; Desai et al, 2022 ). Consequently, individuals in rural areas with deficient sanitation and limited access to safe drinking water are likely at the highest risk of HEV infection ( Mbachu et al, 2021 ; Osundare et al, 2021 ). Among villagers, the prevalence of HEV IgG was 8.7%, which closely resembled the prevalence observed in students (9.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Few HEV studies have been carried out in Nigeria among pregnant women in different states [11][12][13], however, to the best of our knowledge, no single study reported HEV prevalence exclusively among pregnant women in more than one state in each geographical location, to give a true reflection of HEV prevalence among pregnant women in such geographical region. This study, therefore, aimed to focus on the prevalence of hepatitis E virus and the associated risk factors among pregnant women in three (Lagos, Oyo, and Osun) in the six States of the Southwestern geopolitical region in Nigeria.…”
Section: Introductionmentioning
confidence: 91%